2017
DOI: 10.1007/s12630-017-0874-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between the time from oxytocin cessation during labour to Cesarean delivery and postpartum blood loss: a retrospective cohort study

Abstract: Our study shows that an increase in the oxytocin recovery interval is associated with a decrease in blood loss at CD in women with oxytocin augmented labour. These data support discontinuing the oxytocin infusion as soon as the decision is made to proceed with CD for labour arrest, particularly in morbidly obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
(63 reference statements)
0
12
0
1
Order By: Relevance
“…Many authors have found positive associations between PPH and use of oxytocin during labor. 18,20,[25][26][27][28][29][30][31][32] However, in the existing PPH risk assessment tools, prolonged oxytocin exposure is mentioned as a risk factor for hemorrhage. 12 Women in the current study experienced an increased odds of PPH after mean (SD) of 4 (3.0) hours (Induction: Moderate Duration Admission).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors have found positive associations between PPH and use of oxytocin during labor. 18,20,[25][26][27][28][29][30][31][32] However, in the existing PPH risk assessment tools, prolonged oxytocin exposure is mentioned as a risk factor for hemorrhage. 12 Women in the current study experienced an increased odds of PPH after mean (SD) of 4 (3.0) hours (Induction: Moderate Duration Admission).…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to extant literature by quantifying a specific duration of oxytocin infusion that was associated with PPH outcomes during vaginal birth. Many authors have found positive associations between PPH and use of oxytocin during labor 18,20,25‐32 . However, in the existing PPH risk assessment tools, prolonged oxytocin exposure is mentioned as a risk factor for hemorrhage 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Minimizing synthetic oxytocin use and considering decreasing or discontinuing use when active effective labor is established may help maximize oxytocin receptor availability such that women's uteri can respond to endogenous or exogenous postpartum oxytocin. [38][39][40] Strategies for prevention or quick repair of genital tract trauma should be a priority; 41 as it may be an overlooked driver of blood loss. 42 Finally, encouraging endogenous oxytocin release by assisting with early breastfeeding deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Attention to maternal nutrition and hydration will help support effective uterine muscle contraction . Minimizing synthetic oxytocin use and considering decreasing or discontinuing use when active effective labor is established may help maximize oxytocin receptor availability such that women's uteri can respond to endogenous or exogenous postpartum oxytocin . Strategies for prevention or quick repair of genital tract trauma should be a priority; as it may be an overlooked driver of blood loss .…”
Section: Discussionmentioning
confidence: 99%